Methylphenidate for ADHD in Preschoolers - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
The effectiveness of methylphenidate (MPH), 0.3 and 0.5 mg/kg 2x daily, in the treatment of 31 children, aged 4 to 6 years, with attention-deficit hyperactivity disorder (ADHD) was investigated by a double-blind, placebo-controlled study at the University of Ottawa, Canada.